A computational geometric / information theoretic method to invert physics-based MEC models attributes for MEC discrimination - Deschaine, L.M.; Nordin, P.; Pintér, Já.D. (Математичні машини і системи, 2011)
The presence of subsurface munitions and explosives of concern (MEC) is a significant issue worldwide. Discrimination of MEC from non-MEC items enables resources be focused on mitigating risk. Geophysical data is collected and physically-based models inverted with the intent that the inverted model parameters form the basis for MEC discrimination. However, MEC discrimination via model inversion has significant difficulties in noisy environments and with uncertain sensor location. Our computational geometric approach is demonstrated to produce an information-rich set of attributes useful for MEC discrimination including the inverted model information content along with valuable additional information not obtainable using the inversion approach.